The three greens: Innovation, finance, and taxes—Performance analysis and future implications - Ke-Cheng Zhang; Adnan Safi; Bilal Kchouri; Arindam Banerjee; Lu Wang (Journal of Innovation & Knowledge)
Addressing climate challenges and achieving the Sustainable Development Goals (SDGs) necessitate a deep understanding of how green policies influence carbon emissions. Therefore, this study explores the impact of green finance, innovation, and taxation on carbon emissions in OECD countries while accounting for economic growth, renewable energy, and energy productivity. Utilizing the method of moment quantile regression analysis, we find that green finance, taxes, and innovation significantly reduce emissions in OECD economies. The impacts of green finance and taxes exhibit an increasing trend, with higher coefficients at higher quantiles. Conversely, green innovation shows a decreasing trend, with coefficients showing lower magnitude at higher quantiles. The results also show that renewable energy and energy productivity significantly mitigate emissions. In contrast, economic growth correlates positively with CO₂ emissions. Our findings highlight the need for robust policies that invest in clean technologies, broaden green financial instruments, and enhance energy efficiency. In line with the frameworks established at COP28, we emphasize the pivotal role of both public and private funding in facilitating the transition to a low-carbon economy.